Cohort Profile: The Shaanxi Blood Donor Cohort in China - Zhang, Lei; Li, Hengxin; Su, Shu; Wood, Erica M.; Ma, Ting; Sun, Yang; Guo, Lingxia; Cheng, Qianke; Gu, Xiaoyun; Wu, Wenjie; Wang, Liqin; Ding, Miao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Purpose The Shaanxi Blood Donor Cohort was set up to investigate the impact of blood donation on the health of donors compared with non-blood donors. The specific aims of the study include (1) identifying the geographical and temporal trends of incidence for diseases in both blood donors and non-blood donors; (2) assessing the impact of environmental exposures, lifestyle, body mass index (BMI) and blood type on disease burdens, stratified between blood donors and non-blood donors; and (3) among blood donors, investigating if regular blood donation has a positive impact on donors’ health profiles, based on a cohort with a mixed retrospective and prospective study design. Participants A total of 3.4 million adults, with an equal number and identical demographic characteristics (year of birth, sex and location of residence) of blood donors and non-blood donors, were enrolled on 2012. The one-to-one matching was conducted through a repeated random selection of individuals without any history of blood donation from the Shaanxi Electronic Health Records. The cohort has been so far followed up to the end of 2018, summing to nearly 24 million years of follow-up. The cohort will be followed up prospectively every 3 years until 2030. Findings to Date Of the 1.7 million blood donors, 418,312 (24.5%) and 332,569 (19.5%) individuals were outpatients and inpatients, accounting for 1,640,483(96.2%) outpatient and 496,061 (29.1%) inpatient visits. Of the same number of non-blood donors, 407,798 (23.9%) and 346,097 (20.3%) individuals were hospital outpatients and inpatients, accounting for 1,655,725 (97.1%) outpatient and 562,337 (33.0%) inpatient visits. The number of outpatient and inpatient visits by non-blood donors was 0.9 and 3.9% higher than those of the blood donors (p < 0.01). Blood donors demonstrate significantly fewer inpatients visits than non-blood donors for major chronic disease categories (p < 0.01). Future Plans We are currently exploring the long term benefits of blood donation on major chronic disease categories and multimorbidities in this large population cohort. The study results are adjusted by the “healthy donor effect.” This cohort study will continue until 2030.